Method for Screening low glycemic rice in the germplasm - CGIAR Research Program on Rice (2021)
The effect of variety, parboiling soaking temperature and steaming time on physicochemical, nutritional and digestive properties of rice have been evaluated. Based on the results, more varieties (released and in the pipeline for release) have been selected and currently being evaluated both for different processing regimes.